2020
DOI: 10.1007/s11116-020-10141-9
|View full text |Cite
|
Sign up to set email alerts
|

How does purchasing intangible services online influence the travel to consume these services? A focus on a Chinese context

Abstract: A considerable number of empirical studies have explored the effects of information & communication technologies (ICT) on travel in recent years. In particular, the most attention has been paid to whether the use of ICT increases or decreases trip frequency (i.e., substitution or complementarity effects). However, the subject of whether or how travel distance and mode choice are altered by ICT (i.e., modification effects) has almost been ignored. Against this background, using data collected in Beijing, China,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 60 publications
(85 reference statements)
0
36
0
Order By: Relevance
“…Similar substitution findings were made by Hiselius et al (2015), where online shoppers travelled shorter distances by car but there were no differences for other modes. Both articles by Shi, Cheng et al (2020, using the same data, found a modification effect where users of online intangible services (e.g. eating out, visiting moving theatres) travelled longer one-way distances in general.…”
Section: Travel Distancementioning
confidence: 88%
See 2 more Smart Citations
“…Similar substitution findings were made by Hiselius et al (2015), where online shoppers travelled shorter distances by car but there were no differences for other modes. Both articles by Shi, Cheng et al (2020, using the same data, found a modification effect where users of online intangible services (e.g. eating out, visiting moving theatres) travelled longer one-way distances in general.…”
Section: Travel Distancementioning
confidence: 88%
“…This is consistent with Bjerkan et al (2020), who found that online shoppers were more likely to walk or bike. Shi, Cheng et al (2020), studying intangible services, found the opposite: shoppers switched from walking and bicycling to car and public transport. Etminani-Ghasrodashti and Hamidi (2020) showed that online shopping is negatively associated with car and public transport use for shopping travel.…”
Section: Travel Mode Choicementioning
confidence: 99%
See 1 more Smart Citation
“…One study (Bhat et al 2003 ) with longitudinal data also found a combination of the two effects (i.e., substitution and complementarity). A few studies found modification effects (Shi et al 2020a , 2020b ) when measuring changes in travel distances of online shoppers. Some studies also indicated the co-presence of multiple effects, such as complementarity and substitution (Etminani-Ghasrodashti and Hamidi 2020 ; Farag et al 2007 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the internet is unavailable, they usually face more difficulties in acquiring service information or partaking trips to consume them. When purchasing services online, they can easily access massive service information and plan travel routes via the internet (Farag et al, 2006;Shi et al, 2020a), thus making the purchasing process and consuming trips effortless. Consequently, non-urban consumers are expected to have more gain from online buying compared to their counterparts in urban areas, hence making more frequent online purchases likely (Anderson et al, 2003).…”
mentioning
confidence: 99%